Evolution of cellular dislocation structures and defects in additively manufactured austenitic stainless steel under ion irradiation. (15th March 2020) - Li, Shilei; Hu, Jing; Chen, Wei-Ying; Yu, Jingyue; Li, Meimei; Wang, Yandong
Abstract: The evolution of irradiation-induced defects in additively manufactured (AM) austenitic stainless steel was investigated in situ by 1 MeV Kr ion irradiation at 450 and 600 °C in a transmission electron microscope. Cellular dislocation structure in AM steel act as sink/trap sites for the irradiation-induced defects, resulting in the lower density and smaller dislocation loops in AM steel than conventional forged (CF) steel at 450 °C. The higher stacking fault energy and local stress concentration induced by cellular dislocation structure in AM steel promotes the unfaulting process and the formation of network dislocation at 600 °C. Graphical abstract: Image, graphical abstract